Assessing vulnerability of agriculture system to climate change in the SAARC region - Ram Kumar Singh (Elsevier, 2021)
Agriculture production is primarily influenced by human-induced management interventions whereas climate plays an important role. Climate change with increasing global carbon dioxide concentration and changes in temperature, precipitation and other climatic parameters play a significant role in influencing agriculture productivity. The assessment of the vulnerability of agriculture production under the influence of climate change can be done using process-based vegetation models. We assessed the vulnerability of agriculture production for the South Asian Association for Regional Cooperation (SAARC) nations comprising of Afghanistan, Bangladesh, Bhutan, India, Nepal, Maldives, Pakistan and Sri Lanka using the Joint UK Land Environment Simulator (JULES) model. Net Primary Productivity (NPP) was simulated under the forcing of climatic variables of the climate change scenarios of representative concentration pathways (RCP2.6, 4.5 & 8.5) for the year 2050 using JULES. JULES is a process-based model that simulates fluxes of carbon, energy, and momentum between the atmosphere, land surface, and water to estimate the productivity of a system. The sensitivity was calculated as the inter-annual dispersion from the average NPP of assessment period 2016 to 2050, whereas adaptive capacity was calculated as the slope of productivity regressed over the assessment period. The vulnerability was calculated by subtracting the values of adaptability from sensitivity. The JULES simulated NPP was also compared with Moderate Resolution Imaging Spectrometer (MODIS 17A) derived NPP for the period 2000–2014. The simulated NPP had a decreasing trend under projected climate change scenarios of 2050 for all the SAARC nations compared to recent years average of 2000–2014. The analysis reveals that one-third of the SAARC region is highly sensitive under low to moderate emission scenarios, while it was observed that under high emission scenarios the sensitivity would reduce with increased vulnerability. We observed that the vulnerability of the system is not alone influenced by sensitivity and any change in adaptive capacity or resilience would also impact the overall vulnerability of the system.